Cross-cultural adaptation, reliability and validity of the Spanish version of the Upper Limb Functional Index - Cuesta-Vargas, Antonio; Gabel, Charles Philips (BMC Springer Nature, 2013)
Background: The Upper Limb Functional Index (ULFI) is an internationally widely used outcome measure with robust, valid psychometric properties. The purpose of study is to develop and validate a ULFI Spanish-version (ULFI-Sp). Methods: A two stage observational study was conducted. The ULFI was cross-culturally adapted to Spanish through double forward and backward translations, the psychometric properties were then validated. Participants (n = 126) with various upper limb conditions of >12 weeks duration completed the ULFI-Sp, QuickDASH and the Euroqol Health Questionnaire 5 Dimensions (EQ-5D-3 L). The full sample determined internal consistency, concurrent criterion validity, construct validity and factor structure; a subgroup (n = 35) determined reliability at seven days. Results: The ULFI-Sp demonstrated high internal consistency (α = 0.94) and reliability (r = 0.93). Factor structure was one-dimensional and supported construct validity. Criterion validity with the EQ-5D-3 L was fair and inversely correlated (r = -0.59). The QuickDASH data was unavailable for analysis due to excessive missing responses. Conclusions: The ULFI-Sp is a valid upper limb outcome measure with similar psychometric properties to the English language version.
Keywords: Miembros superiores - Test; Upper limb; Psychometrics; Outcome measure; Spanish